António Campos, o insubmisso: uma veia do amador no registro documentário - Ramos, Guiomar (2022)
The purpose of this article is to reflect on the process of the creation of António Campos from the idea of the amateur film, extracting from it its aesthetic power. The article discusses the power of his stylistic considering the definitions of documentary and experimental or inventive film.